THE INFLUENCE OF IPL AND TNPL IN THE CRICKETING PSYCHOLOGY OF THE PLAYERS IN TAMIL NADU - D, Prasanna Balaji.; Mahesh, K. (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to study the resultant factors linked to the success of Indian Premier League and its influence in regional cricket. It also aims to find out the impact of these ensuing factors in the rise of Tamil Nadu Premiere League and the reaction of the regional cricketers. With a set of questions prepared to identify the attitude of cricketers, the study aims at unearthing the real spirit of the people of Tamil Nadu towards cricket. The response of the players have been analysed with visual representations and the findings have been clearly stated at the end.